The limits of ex post implementation without transfers - Tangren Feng; Axel Niemeyer; Qinggong Wu (Theoretical Economics, 2023)
We study ex post implementation in collective decision problems where monetary transfers cannot be used. We find that deterministic ex post implementation is impossible if the underlying environment is neither almost an environment with private values nor almost one with common values. Thus, desirable properties of ex post implementation such as informational robustness become difficult to achieve when preference interdependence and preference heterogeneity are both present in the environment.
Keywords: D82; D71; 330; collective decision-making; Ex post implementation; informational robustness; interdependent values; mechanism design; nontransferable utility